Outcomes for patients with rheumatic heart disease after cardiac surgery followed at rural district hospitals in Rwanda. Issue 20 (20th April 2018) - Rusingiza, Emmanuel K; El-Khatib, Ziad; Hedt-Gauthier, Bethany; Ngoga, Gedeon; Dusabeyezu, Symaque; Tapela, Neo; Mutumbira, Cadet; Mutabazi, Francis; Harelimana, Emmanuel; Mucumbitsi, Joseph; Kwan, Gene F; Bukhman, Gene
Abstract : Background: In sub-Saharan Africa, continued clinical follow-up, after cardiac surgery, is only available at urban referral centres. We implemented a decentralised, integrated care model to provide longitudinal care for patients with advanced rheumatic heart disease (RHD) at district hospitals in rural Rwanda before and after heart surgery. Methods: We collected data from charts at non-communicable disease (NCD) clinics at three rural district hospitals in Rwanda to describe the outcomes of 54 patients with RHD who received cardiac valve surgery during 2007–2015. Results: The majority of patients were adults (46/54; 85%), and 74% were females. The median age at the time of surgery was 22 years in adults and 11 years in children. Advanced symptoms—New York Heart Association class III or IV—were present in 83% before surgery and only 4% afterwards. The mitral valve was the most common valve requiring surgery. Valvular surgery consisted mostly of a single valve (56%) and double valve (41%). Patients were followed for a median of 3 years (range 0.2–7.9) during which 7.4% of them died; all deaths were patients who had undergone bioprosthetic valve replacement. For patients with mechanical valves, anticoagulation was checked at 96% of visits. There were no known bleeding or thrombotic events requiring hospitalisation. Conclusion: Outcomes of postoperative patients with RHD tracked in rural Rwanda health facilities were generally good. With appropriate training and supervision, it is feasible to safely decentralise follow-up of patients with RHD to nurse-led specialised NCD clinics after cardiac surgery.